2020
DOI: 10.28982/josam.737088
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 pandemic on sleeping status

Abstract: All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments. Etik Kurul Onayı: Etik kurul onayı İstanbul Yeni Yüzyıl Üniversitesi, Fen Bilimleri, Sosyal ve Girişimsel Olmayan Sağlık Bilimleri Araştırmaları Etik Kurulu'ndan (Sayı: 2020/04-05) alınmıştır. İnsan katılımcıların katıldığı çalışmalardaki tüm prosedürler, 1964 Helsinki Deklarasyonu ve daha sonra yapılan değişiklikler uyarınca gerçekleştirilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
(13 reference statements)
1
12
0
5
Order By: Relevance
“…According to the results of the regression analysis, it was concluded that Covid-19 anxiety affected the professional performance levels of the participants by 30%. (Maguire vd., 2007;Silverman vd., 2004 (Taylor vd., 2008;Wang vd., 2020;Erdoğdu vd., 2020;Özdin ve Özdin, 2020;Polat ve Coşkun, 2020;Evren vd., 2020;Demir, 2020;Havlıoğlu ve Demir, 2020) Kasım 2020 November…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of the regression analysis, it was concluded that Covid-19 anxiety affected the professional performance levels of the participants by 30%. (Maguire vd., 2007;Silverman vd., 2004 (Taylor vd., 2008;Wang vd., 2020;Erdoğdu vd., 2020;Özdin ve Özdin, 2020;Polat ve Coşkun, 2020;Evren vd., 2020;Demir, 2020;Havlıoğlu ve Demir, 2020) Kasım 2020 November…”
Section: Results and Conclusionmentioning
confidence: 99%
“…mevcut olduğu gibi, erkekler lehine farklılık bulan(Kuru ve Uymaz, 2020) ve bunun aksine değişkenler arasında herhangi bir anlamlı farklılık saptamayan çalışmalar(Zhang vd., 2020; Özdede ve C. Şahin, 2020) da mevcuttur. Havlıoğlu veDemir (2020)'in çalışmasında ise, bu çalışmadan farklı olarak, Covid-19 anksiyetesi ve mesleki deneyim süresi arasında anlamlı bir farklılık olmadığı ortaya konulmasına rağmen, sağlık yönetimi yazınında mesleği severek yapıp yapmama durumu ile anksiyete arasındaki ilişkileri araştıran herhangi bir çalışmaya rastlanmamıştır. Mevcut çalışmada katılımcıların medeni durumları, herhangi bir kronik hastalığa sahip olup olmama durumları, Covid-19 tanısı almış olup olmadıkları, eğitim düzeyleri ve mesleki unvanları ile Covid-19 Anksiyetesi Ölçeği puan ortalamaları arasında anlamsız farklılıklar olduğu sonucuna varılmıştır.…”
unclassified
“…COVID-19 has affected individuals worldwide. However, individuals also have to cope with financial and social disturbances during this period [5]. Its clinical manifestations vary; it can be asymptomatic, mild or severe.…”
Section: Discussionmentioning
confidence: 99%
“…While the measures that have been implemented by governments and healthcare organizations to slow the fast spread of the disease, such as lockdowns, mandatory isolation, quarantines, and temporary closures, are necessary for disease control and reducing the effect of the disease on the healthcare system, one of the drawbacks of these measures is the disruption they cause to the sleep-wakefulness cycle [2][3][4].…”
Section: Introductionmentioning
confidence: 99%